Energetic Electron Enhancements below the Radiation Belt and X-Ray Contamination at Low-Orbiting Satellites. (8th October 2014) - Suvorova, Alla V.; Dmitriev, Alexei V.; Huang, Chien-Ming
Abstract : The work concerns a problem of electron-induced contaminant at relatively low latitudes to high-energy astrophysical measurements on board the low-orbiting satellites. We show the results of a statistical analysis of the energetic electron enhancements in energy range 30–300 keV observed by a fleet of NOAA/POES low-orbiting satellites over the time period from 1999 to 2012. We demonstrate geographical distributions of great and moderate long-lasting enhancements caused by different type of the solar wind drivers.